2004
DOI: 10.1515/cclm.2004.030
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against oxidized low-density lipoprotein (ox-LDL) and LDL oxidation status

Abstract: Oxidized low-density lipoproteins (ox-LDLs) and their autoantibodies (OLAB) are involved in the development of atherosclerosis in animal models, but their role in humans is still not clear. For this reason we studied 54 patients with beta-thalassemia major (TM), as a model of chronically low circulating LDLs with a high level of oxidation; 44 patients with primary hypercholesterolemia, as model of chronically high circulating LDLs; 24 type 2 diabetic mellitus patients (T2DM) before and after 3 months of atorva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…Other studies have found that circulating LDL of b-TM patients are more susceptible to oxidation not only due to iron overload but also due to decreased HDL levels in those patients (20). Moreover, Brizzi et al (19) reported that in b-TM patients, since iron overload depletes the antioxidant and HDL-C is lower than normal, then LDL composition is mainly influenced by the TG level.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies have found that circulating LDL of b-TM patients are more susceptible to oxidation not only due to iron overload but also due to decreased HDL levels in those patients (20). Moreover, Brizzi et al (19) reported that in b-TM patients, since iron overload depletes the antioxidant and HDL-C is lower than normal, then LDL composition is mainly influenced by the TG level.…”
Section: Discussionmentioning
confidence: 96%
“…Although serum LDL may be normal or high in thalassemic patients, it is subjected to peroxidative stress due to iron overload secondary to blood transfusions that could represent an event leading to atherosclerogenesis (19). Moreover, steatosis and chronic viral hepatitis induce hepatic acutephase response, which is associated with an enhanced LDL secretion (20). An important role of unpaired Hb chains and red blood cell hemolysis products are also under consideration since it has been observed that the interaction between Hb a chain and LDL leads to the oxidative modification of LDL (21).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OLAB levels appear to be negatively correlated with indices of oxidative stress [23] and negatively associated with the severity and extent of stenotic coronary lesions [24]. Therefore, OLAB may protect against atherosclerosis by attenuating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, a significant inverse correlation between the presence of anti-oxLDL autoantibodies and the degree of LDL or LDL oxidation was demonstrated (45), suggesting that the increase in anti-oxLDL antibodies and the extent of the LDL oxidation ratio is protective against atherosclerosis. The findings are indeed conflicting, since some anti-oxLDL autoantibodies seem to be protective, whereas many others are found to be correlated with the extent of atherosclerosis; thus, antioxLDL can be characterized as either predictive or pathogenic.…”
Section: Protective Antibodies In Autoimmune Diseasesmentioning
confidence: 95%